2022
DOI: 10.1094/phyto-06-21-0269-r
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Application of Tailocins Prevents Infection by Pseudomonas syringae

Abstract: Tailocins are phage-derived bacteriocins that demonstrate great potential as agricultural antimicrobials given their high killing efficiency and their precise strain-specific targeting ability. Our group has recently categorized and characterized tailocins produced by and tailocin sensitivities of the phytopathogen Pseudomonas syringae, and here we extend these experiments to test whether prophylactic tailocin application can prevent infection of Nicotiana benthamiana by P. syringae pv. syringae B728a. Specifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…syringae pv. syringae B728a ( Psy B728a) [8], and we further confirm killing of all these strains against Psy B728a here (). Furthermore, all strains also appear to have the same efficiency of activity against P.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…syringae pv. syringae B728a ( Psy B728a) [8], and we further confirm killing of all these strains against Psy B728a here (). Furthermore, all strains also appear to have the same efficiency of activity against P.…”
Section: Resultssupporting
confidence: 83%
“…Previous research suggested that the intraspecific killing spectrum of these tailocins is specific across closely related strains within the P. syringae complex [8, 25], but here we expand on these results and report that the killing activity of tailocins produced by P. syringae strain USA011R can be interspecific.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations